Coagulation Profiles Are Associated With Early Clinical Outcomes in Neonatal Encephalopathy - Sweetman, Deirdre; Kelly, Lynne A.; Zareen, Zunera; Nolan, Beatrice; Murphy, John; Boylan, Geraldine; Donoghue, Veronica; Molloy, Eleanor J. (Frontiers in Pediatrics, 2019)
Objective: Neonatal encephalopathy (NE) is associated with coagulation abnormalities. We aimed to investigate the serial alterations in coagulation profiles in term infants with NE and correlate with clinical outcomes. Methods: Prospective cohort study in a tertiary referral, university-affiliated maternity hospital. Neonates exposed to perinatal asphyxia were recruited (n=82) and 39 received therapeutic hypothermia. Infants had serial coagulation tests including platelets, prothrombin time (PT), activated partial thromboplastin time (aPTT) and fibrinogen in the first week of life. The main outcome measures included MRI brain and EEG seizures. Results: Mortality was predicted on day 1 by decreased Fibrinogen (AUC= 0.95, p-value = 0.009) and by PT on day 2 with a cutoff of 22 seconds. An abnormal MRI was predicted by Fibrinogen on day 3 with a cut-off value of 2 g/L. For prediction of grade II/III NE, PT on day 2 of life was strongest with a cut-off value of 14 secs. Only elevated APTT levels on day 1 of life were predictive of seizures (AUC = 0.65, p-value = 0.04). Conclusions: Coagulation parameters are strong predictors of outcomes such as abnormal NE grade, seizures and mortality.